TINJAUAN SIYASAH DUSTURIYAH TERHADAP PEMBERHENTIAN PERANGKAT NAGARI OLEH WALI NAGARI DI NAGARI BARULAK BERDASARKAN PERDA KABUPATEN TANAH DATAR NO 5 TAHUN 2018 - Hesti Julianti Saputri; Emrizal Emrizal; Saadatul Maghfira; Dian Pertiwi (Institut Agama Islam Negeri Batusangkar, 2023)
The problem in writing this thesis is to examine the rules regarding procedures or rules for dismissing nagari officials. The purpose of this research is to find out and explain the mechanism for dismissing the nagari apparatus by the Wali Nagari and to find out and analyze the siyasah dusturiyah review of the dismissal of the nagari apparatus. To answer the object of study in this study, the authors use the type of normative legal research or (Library research), namely research that explores law as norms, rules, legal principles, legal principles, legal doctrine, and legal theory. Therefore, this research was conducted by examining library materials to answer legal issues regarding the nagari dismissal system carried out by the Wali Nagari in Nagari Barulak and the perspective of fiqh siyasah dusturiyah through data obtained from the literature. This normative legal research uses a qualitative typology, namely a literature search which is analyzed and described in a comprehensive manner related to the dismissal system of the nagari apparatus carried out by the Wali Nagari in Nagari Barulak. The results of this study: nagari devices that have been determined by the rules. A review of siyasa dusturiyah fiqh in the topic of study Siyasa Qadha'iyah emphasizes that leaders should supervise and guarantee the implementation of statutory values in the community sphere. However, the Wali Nagari Barulak as the leader has made a decision that has violated the law. As well as indirectly his actions have violated the values or mandate of the Al-Quran and the Prophet's Hadith regarding justice and leadership principles.